Special Issue "Gut Microbiota, Inflammatory Bowel Diseases, and Therapeutic Targets" - Eirini Filidou; George Kolios (MDPI AG, 2023)
The gut microbiota and its overall genetic composition, the microbiome, have been the subject of extensive research over the last decade within the fields of genomics, transcriptomics and metabolomics, and their role in various other targeted approaches and advanced technologies has been explored [...]